Uterine Involution in Nubian Goats Monitored by Ultrasonography (Journal of Veterinary Medicine and Animal Production, 2022)
Twelve postpartum Nubian goats were used to monitor the uterine involution using ultrasonography on days 3, 7, 10, 14, 21, 24, 27 and 31 postpartum (pp). The maximum and minimum means of uterine diameter (UD) and uterine lumen (UL) were recorded on day 3 and day 31 pp, respectively. More than 50% of uterine involution occurred between day 3 and day 14 pp. The end of uterine involution was characterized by small UD and absence of lochia in the UL. The uterine involution was completed at 22 days pp.It could be concluded that Ultrasonographic imaging proved to be a valuable tool for monitoring uterine involution in Nubian goats. There is a positive correlation between UD and UL.
Keywords: : Postpartum; Uterine involution; Ultrasonography; Nubian goats